Spatiotemporal analysis of extreme precipitation events in the Northeast region of Argentina (NEA) - Lovino, Miguel Angel (2014)
Study region: An area in NEA located within the La Plata Basin (LPB) where extreme precipitation events (EPE) are the most harmful and costly natural disasters. Study focus: The study analyzes the spatiotemporal behavior of EPE through a Principal Component Analysis (PCA) applied to fields of Standard Precipitation Index (SPI) at different time scales. The vulnerability of the NEA to EPE was estimated by defining the portion of the region experiencing extremely dry/wet conditions in critical months. Singular Spectrum Analysis (SSA) was applied to the time series looking for significant trends or oscillatory modes. New hydrological insights for the region: The spatial average SPI series show a positive nonlinear trend with changes to wetter conditions from 1960 to2000s, subsequent signs of stabilization and a trend reversal since 2007. The most severe hydrological and agricultural droughts occurred between 1901and 1960 while the larger wet EPE were recorded between 1970 and 2005. Moreover, a prolonged dry period was registered between 1921 and 1939 that might extend the “Pampas Dust Bowl” to the bulk of the NEA. The EPE show cycles of 6.5 and 8.7 years together with a quasi-decadal cycle in the Northwestern corner. Our results suggest that almost the entire NEA is highly vulnerable to EPE at a time scale relevant for agricultural activities and the Central-West portion is particularly vulnerable to hydrological EPE.